Knowledge Management in Human Resource in Oil Companies from Technologies Perspectives a Literature Review - Almalky, Nabil; Ikeda, Mitsuru; Umemoto, Katsuhiro (International Journal of Engineering and Technology, 2019)
The aim of the current work is to discuss how has human resource (HR) and knowledge management (KM) technologies been developed in oil and gas industry. In order to fulfil this aim, four sub questions were formulated, which sought to understand: how technologies are supporting KM activities, HR activities, cultural KM relations, and the relations between HR and KM. This was done with the main purpose of coming up with a model that explains the development of HR and KM technologies. The study assumed a secondary approach wherein secondary data from peer reviewed studies were used in coming up with the findings. The different studies used in coming up with the findings were discussing how knowledge management has developed in the field of HR also the significance of understanding the oil and gas industry HRKM Technologies. According to the findings of the research, the importance of the developed Framework /Model for HR and KM can summarized into three major points: (1) there are the unique meanings of the term KM strategy; (2) the normal use of correlation of technologies to knowledge processes in the past studies has not adequate enough to explain their links to business strategy; and (3) technologies applied in KM can be used together in many different levels. The findings suggested contingency approach, which centres on KM initiatives, might be helpful when it comes to explaining the manner in which KM technologies can support strategy.